ANALISIS STRATEGI BISNIS DALAM MENINGKATKAN MARKET SHARE DENGAN MENGGUNAKAN PENDEKATAN ANALYSIS BUSINESS MODEL CANVAS (BMC) DAN SWOT ANALYSIS PADA PT. SEMEN INDONESIA DISTRIBUTOR DI PURWODADI - Agus Widodo (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2020)
This study aims to analyze the business strategies implemented at PT Semen Indonesia Distributor in the face of changes in the market competition map for market share and to determine business strategies that have a competitive advantage in increasing the market share of Semen Gresik amid increasingly fierce market competition. The emergence of business strategy gaps, market share gap, canvas model business gap, SWOT analysis gapThe type of my research is qualitative research, namely a research method based on the philosophy of postpositivism, used to examine the conditions of natural objects, where the researcher is an instrument, the sampling of data sources is carried out by probability sampling. The collection technique is done by using Disproportionate Stratified Random Sampling, and triangulation (combined). Data analysis of business strategies in increasing market share is done by using a business model canvas analysis approach and SWOT analysis.The results of the research conducted show that through the Business Model Canvas (BMC) approach and SWOT analysis, it is found that the main cause of the market share at PT Semen Indonesia Distributor Purwodadi Branch does not increase significantly even tends to stagnate, as illustrated in the analysis of the strengths and weaknesses of the implementation of the elements of the Business Model. Canvas and analysis of opportunities and threats from external factors of the company. Based on the results of the Grand Strategy Matrix analysis, it shows that the company is in Quadrant I which is a suitable strategy to be implemented in PT. Semen Indonesia Distributor Purwodadi Branch is a cooperation strategy through vertical integration and market expansion strategy through conglomerate diversification. Meanwhile, the results of the Quantitative Strategies Planning Matrix (QSPM) analysis show that among the aggressive alternative growth strategies (gaining new market share (new segmentation), rewarding the marketing team) that have been formulated, the QSPM results provide a higher value than the strategy other.